Values, lifestyles, and narratives of prejudices amongst Finnish youth. Issue 1 (2nd January 2023) - Koirikivi, Pia; Benjamin, Saija; Kuusisto, Arniika; Gearon, Liam
ABSTRACT: Prejudices are innate to the human condition and at the base of most conflicts between social groups. Yet, despite much local and global educational effort to promote equality and peace, expressions of hate and violence are omnipresent across the globe. For gaining more understanding about the complex relationship between values and beliefs that influence people's prejudiced attitudes towards others, this study investigates how Finnish upper-secondary level students (16- to 20-year-olds), on the one hand, affiliate themselves with self-transcendent values, and on the other hand, narrate prejudices towards others. The complementary quantitative (n = 2873) and qualitative (n = 2200) survey responses show that the young people regarded equality and the promotion of peace as the most important values for themselves but, despite this explicit appreciation of these self-transcendent values, they also exhibit several types of prejudice towards others. The findings show that the youth narratives of prejudices are mainly justified with their prior experiences, their imaginaries related to insecurity, disturbances, and conflicts with people who they deem to have lifestyles different from their own. This study expands existing knowledge by suggesting that the main rationales behind young people's prejudices are not based on traditional social categorisations, or core values, but on differences expressed through individual lifestyles.